Optimization of Balanced Menu for Pregnant Women in Grobogan-Central Java using Simplex Method - Nihaya Alivia Coraima Dewi; Fitroh Resmi; Pukky Tetralian Bantining Ngastiti (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
This study aims to determine the optimization of balanced dietary composition for pregnant women. Determination of the optimization of balanced food is carried out by forming a linear model along with boundary conditions and objective functions, as well as inputting data on the age of pregnant women, age of pregnancy and maternal nutritional needs, then the calculation is carried out using the simplex method in order to obtain the weight of food ingredients that must be consumed to get a balanced nutrition, namely with 75 combinations that have been analyzed on groups of pregnant women aged 19-29 years and 30-49 years in three trimesters, including staple foods, vegetables (spinach, green mustard, cauliflower, kale, carrots), fruit, side dishes vegetables, nuts, sugar and milk with the recommended nutritional adequacy rate for the data content of water, energy, protein, fat, carbohydrate (KH), fiber, vitamin A, B1, B2, B3 and vitamin C. In the group of pregnant women aged 19-29 years and women aged 30-49 years in the three trimesters, it was found that the combination of 55 was the optimal combination with rice, kale, watermelon, and tofu.